Pre School of School Children Development in Bandung District, West Java Province - Indriyani, Yuni; Saraswati, Aas (Universitas Pendidikan Ganesha, 2018)
Community Partnership Program Objectives on workshoop activities to improve teacher and parent understanding of children's development in accordance with the stages of development. Specific targets expected from this activity are teachers and parents understanding and knowing the stages of development so that they can provide stimulus and the potential that exists in children to develop optimally. The target of the community in this service is the teachers and parents in RA Daarus Syifa and RA Tazkya totaling 100 people. Activities are carried out from April to August 2018. Methods of implementing activities are observation, implementation of activities, assistance and evaluation. From the results of the reflection obtained from the results of this community service activity is to increase the knowledge of teachers and parents in child development. By providing assistance, the teacher will understand the stages of development in the learning process. This activity should be carried out on a broader target, so that it can help teachers in developing children's development, especially in the learning process.